Metamorphōsis Between Ovid, The Theōsis Of Andrew Of Crete And The Byzantine Humanism Of Leo Vi - Jan Dominik Bogataj (Keria: Studia Latina et Graeca, 2019)
The paper addresses the Greek term μεταμόρφωσις, which links Ovid’s famous Metamorphoses with Christ’s transfiguration on the mountain (Mt 17:1–8; Mk 9:2–8; Lk 9:28–36). In addition to early Jewish mystical and apocalyptic traditions, it is Greco-Roman pagan literature that may be identified as a source for this gospel account. The latter went on to elicit a rich patristic and Byzantine response (Andrew of Crete, In transfigurationem 1 [Or. 7]; Leo VI the Wise, Hom. 10.11.39), which is the focus of the present study. The comparison of literary genres, philological and semantic analysis of the term μεταμόρφωσις, and confrontation of the different influences reveals the crucial difference between the two general contexts (pagan and Christian), at the same time enhancing our understanding of both. While Ovid’s numerous apotheoses are recognised as an important contribution, they differ from the patristic term θέωσις in their lack of inner, spiritual transformation.